Prevalence of proteinuria in a canine oncology population. (2nd April 2018) - Prudic, R. A.; Saba, C. F.; Lourenço, B. N.; Bugbee, A. C.
Abstract : Objective: To evaluate the point prevalence of proteinuria in dogs presenting to the University of Georgia Oncology Service for the first time. Materials and Methods: In this prospective study, 60 client‐owned dogs with a confirmed cancer diagnosis were included but those with lower urinary tract neoplasia were excluded. Each dog's signalment, cancer diagnosis, previous cancer treatments, current medications and travel history were recorded. Renal values, electrolytes, packed cell volume, total solids, systolic blood pressure, urinalysis, urine protein:urine creatinine and retinal examinations were recorded. Non‐proteinuric, borderline proteinuria and overt proteinuria were defined as urine protein:urine creatinine <0·2, ≥0·2 but <0·5, and ≥0·5, respectively. Urine culture was performed in dogs with active urine sediments or overt proteinuria. Results: Twenty‐nine dogs were non‐proteinuric (48·3%), 22 (36·7%) borderline proteinuric and nine (15%) overtly proteinuric. None were azotaemic. Hypertension (systolic blood pressure ≥160 mmHg) was detected in 18 (30%) dogs. Of these, six were non‐proteinuric, nine borderline proteinuric, and three overtly proteinuric. Proteinuria was detected in 51% of dogs presented to our oncology service, the majority of which were classified as borderline. Clinical Significance: The high proportion of proteinuria in dogs in this study suggests that screening for proteinuria in dogs with cancer may be prudent. Larger studies are required to correlate specific cancer types and the impact of treatment with the development, magnitude and persistence of proteinuria.